1985
DOI: 10.1212/wnl.35.3.394
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia in dementia of the Alzheimer type

Abstract: Speech and language assessment in 30 patients with dementia of the Alzheimer type and in 70 normal controls revealed that all Alzheimer patients were aphasic. Throughout most of the course, the language disorder resembled transcortical sensory aphasia, and increasing language impairment correlated with increasing severity of dementia. Aphasia was present regardless of age of onset or family history of dementia. Aphasia is an important diagnostic criterion of dementia of the Alzheimer type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
0
10

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(126 citation statements)
references
References 0 publications
7
109
0
10
Order By: Relevance
“…Several studies did not find any distinctive differences between EOAD and LOAD patients (Cummings et al, 1985;Bayles et al, 1987;Grady et al, 1987;Selnes et al, 1988;Toyota et al, 2007) or have attributed such differences to dementia severity (Jacobs et al, 1994;Smits et al, 2012). Regarding memory, a relative sparing of memory in EOAD has been reported (Binetti et al, 1996;Smits et al, 2012), while several studies have found that LOAD patients present primarily with memory difficulties (Jacobs et al, 1994;Imamura et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies did not find any distinctive differences between EOAD and LOAD patients (Cummings et al, 1985;Bayles et al, 1987;Grady et al, 1987;Selnes et al, 1988;Toyota et al, 2007) or have attributed such differences to dementia severity (Jacobs et al, 1994;Smits et al, 2012). Regarding memory, a relative sparing of memory in EOAD has been reported (Binetti et al, 1996;Smits et al, 2012), while several studies have found that LOAD patients present primarily with memory difficulties (Jacobs et al, 1994;Imamura et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…En primer lugar, el hecho de que las tareas de naturaleza verbal, como la fluidez y la memoria lógica discriminen mejor el deterioro cognitivo de lo que no lo es concuerda con los resultados obtenidos por diversos autores (Cummings, Benson y Hill, 1985;Kertesz, Appel y Fisman, 1986;Hart, Kwentus, Taylor y Harkins, 1987;Emery, 1992). En segundo lugar, el hecho de que la metamemoria se deteriore significa-tivamente en los deprimidos muestra por qué muchos sujetos con depresión acuden a las consultas generales o especializadas con el temor a sufrir algún tipo de demencia, resultado que confimna lo hallado por otros autores (Bazargan y Barbre, 1994;McDougall, 1994;Dellefield y McDougall, 1996).…”
Section: Discussionunclassified
“…The common symptoms are: memory loss, confusion, irritability, aggression, trouble with language, and mood swings [26]. The most significant effect on functional communication skills that accompanies Alzheimer's disease (AD) is aphasia [27], a loss of oral communicative ability like breakdowns in semantic processing, shallow vocabularies and word-finding difficulties leading to the deterioration of spontaneous speech [28]. The Mini-Mental State Exam (MMSE) is a cognitive grading scale used in the assessment of patients first described by Folstein et al [29] in 1975 and Verbal picture descriptions later became the other precise measures for assessing spontaneous speech in AD.…”
Section: 2mentioning
confidence: 99%